Microalgae Cultivation in Pilot Scale for Biomass Production Using Exhaust Gas from Thermal Power Plants - Park, Sanghyun; Ahn, Yongtae; Pandi, Kalimuthu; Ji, Min-Kyu; Yun, Hyun-Shik; Choi, Jae-Young (MDPI, 2019)
Exhaust gases from thermal power plants have the highest amount of carbon dioxide (CO2), presenting an environmental problem related to a severe impact on ecosystems. Extensively, the reduction of CO2 from thermal power plants has been considered with the aid of microalgae as a cost-effective, sustainable solution, and efficient biological means for recycling of CO2. Microalgae can efficiently uptake CO2 and nutrients resulting in high generation of biomass and which can be processed into different valuable products. In this study, we have taken Nephroselmis sp. KGE8, Acutodesmus obliquus KGE 17 and Acutodesmus obliquus KGE32 microalgae, which are isolated from acid mine drainage and cultivated in a photobiological incubator on a batch scale, and also confirmed that continuous culture was possible on pilot scale for biofuel production. We also evaluated the continuous culture productivity of each cultivate-harvest cycle in the pilot scale. The biomass of the cultivated microalgae was also evaluated for its availability.